‘Modernisation without modernism’: changes in polish criminal procedure in the last decade and visions of the criminal process of the future (Ius Novum, 2025)
The legislatively complex fate of Polish criminal law, including criminal procedure, over the last ten years, as well as the currently open prospect of further reforms in this area, prompts one to reflect from a distance on how these multidirectional changes position themselves within the broader trends in the development of the criminal process worldwide, and to what extent the Polish criminal process is in fact being ‘modernised’ in its essence, rather than merely ‘modernised’ in a technological sense. This reflection leads to the question of how these ‘modernisations’, regardless of their level, relate to the functioning of the Polish criminal process in the postmodern era and whether postmodernism, as an intellectual current, can offer something to the criminal process, especially in the area of the problems that trouble it and require urgent solution. What emerges from the analysis is a picture of legislative randomness and impermanence of changes, and the covering of what is obsolete in Polish criminal procedure with technological novelties in its organisational layer. For this reason, it is vital to urgently discuss the reformist demands being made for criminal procedure – so that they do not remain purely academic considerations, but are translated into real changes to the law and social practices constituting the criminal process.
Keywords: criminal trial, postmodernism, modernisation, postmodernity, adversarial reform, reform of criminal law and procedure, decodification, conflict theory